Adverse events as potential predictive factors of activity in patients with advanced hepatocellular carcinoma treated with lenvatinib. (22nd July 2021) - Rapposelli, Ilario Giovanni; Tada, Toshifumi; Shimose, Shigeo; Burgio, Valentina; Kumada, Takashi; Iwamoto, Hideki; Hiraoka, Atsushi; Niizeki, Takashi; Atsukawa, Masanori; Koga, Hironori; Hirooka, Masashi; Torimura, Takuji; et al.
Abstract: Background and Aim: Lenvatinib is a standard of care option in first‐line therapy of advanced hepatocellular carcinoma (HCC). In the present study, we aim to identify, in patients with HCC treated with lenvatinib, a possible association between occurrence and grading of adverse events (AEs) and outcome. Methods: We performed a retrospective analysis of 606 Japanese and Italian patients treated with lenvatinib in first‐line setting and investigated the possible correlation between the onset of AEs, toxicity grade (G) and outcome measures such as overall survival (OS) and progression‐free survival (PFS). Results: The appearance of arterial hypertension G ≥ 2 independently predicted prolonged OS [hazard ratio (HR) 0.66, 95% confidence interval (CI) 0.46–0.93, P = .0188], whereas decreased appetite G ≥ 2 independently predicted decreased OS (HR 1.70, 95% CI 1.25–2.32, P = .0007) by multivariate analysis. Appearance of hand‐foot skin reaction independently predicted prolonged PFS (HR 0.72, 95% CI 0.56–0.93, P = .0149), whereas decreased appetite G ≥ 2 predicted decreased PFS (HR 1.36, 95% CI 1.04–1.77, P = .0277). Conclusions: Our main findings are that the occurrence of arterial hypertension G ≥ 2 is a predictor of longer survival, whereas decreased appetite G ≥ 2 predicts for a poor prognosis. A careful management of AEs under lenvatinib treatment for HCC is required, to improve patients' quality of life, minimize the need for treatment discontinuation and achieve optimal outcome.